戈利木单抗治疗白塞综合征心脏大血管受累的临床分析 (Beijing Da Xue Xue Bao Yi Xue Ban, 2020)
OBJECTIVE: To explore the effectiveness and safety of golimumab in the treatment of severe/refractory cardiovascular Behcet syndrome (BS). METHODS: We retrospectively analyzed the clinical data of nine patients diagnosed with severe/refractory cardiovascular BS and treated with golimumab from February 2018 to July 2020 in Peking Union Medical College Hospital. We analyzed levels of erythrocyte sedimentation rate (ESR) and high-sensitivity C-reactive protein (hsCRP), imaging findings, and the doses of glucocorticoids and immunosuppressive agents during the period of combined treatment with golimumab. RESULTS: Nine patients were enrolled, including 8 males and 1 female, with a mean age and median course of (37.0±8.6) years and 120 (60, 132) months, respectively. Seven patients presented with severe aortic regurgitation combined with other cardiovascular involvement secondary to BS. Two patients presented with large vessel involvement, including multiple aneurysms and vein thrombosis. Prior to golimumab treatment, seven patients were treated with glucocorticoids and multiple immunosuppres-sants [with a median number of 3 (1, 3) types] while still experienced disease progression or elevated inflammation biomarkers during postoperative period. Eight patients with disease progression, uncontrolled inflammation and history of severe postoperative complications required effective and fast control of inflammation during perioperative period. One patient had adverse reaction with tocilizumab and switched to golimumab during perioperative period. The patients were treated with golimumab 50 mg every 4 weeks, along with concomitant treatment of glucocorticoid and immunosuppressants. After a median follow-up of (16.3±5.6) months, all the patients achieved clinical improvement. Vascular lesions were radiologically stable and no vascular progressive or newly-onset of vascular lesions was observed. The eight patients who experienced cardiac or vascular operations showed no evidence of postoperative complications. The ESR and hsCRP levels decreased significantly [16.5 (6.8, 52.5) mm/h vs. 4 (2, 7) mm/h, and 21.24 (0.93, 32.51) mg/L vs. 0.58 (0.37, 1.79) mg/L (P < 0.05), respectively]. The dose of prednisone was tapered from 35 (15, 60) mg/d to 10.0 (10.0, 12.5) mg/d. No prominent adverse reactions were observed. CONCLUSION: Our study suggests that golimumab is effective in the treatment of severe/refractory cardiovascular BS. Combination immunosuppression therapy with golimumab contributes to control of inflammation, reduction of postoperative complications and tapering the dose of glucocorticoids or immunosuppressants.